Psychometric properties of the persian version of the health professionals education in patient safety survey - Niloufar Alidousti-Shahraki; Sedigheh Farzi; Mohammad Javad Tarrahi (Kashan University of Medical Sciences, 2022)
Background: Safe care requires acquiring special competencies. Suitable instruments are needed to evaluate such competencies. Objectives: This study aimed to assess the psychometric properties of the Persian version of the Health Professionals Education in Patient Safety Survey (H-PEPSS). Methods: A methodological study was conducted in 2020, on the students who were spending their last year of study in nursing, medicine, pharmacy, midwifery, surgical technology, and anesthesia, in the Isfahan University of Medical Sciences. The H-PEPSS was translated into Persian based on the Brislin translation model. Face validity, content validity index (CVI), and content validity ratio (CVR) were examined. The construct validity of the scale was assessed using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Cronbach's alpha coefficient and interclass correlation coefficient were also calculated as reliability criteria. Results: The face validity of the Persian translation of H-PEPSS was confirmed by a panel of experts, and the items' impact scores were greater than 1.5. Three items were modified, and the CVI of the scale was calculated at 0.91. Besides, the items' CVR ranged from 0.64 to 1.00. In EFA, six factors were extracted, which shows the competencies the students possessed both in the classroom and clinical setting, which then were confirmed through the CFA. All items had a factor loading value greater than 0.4. Goodness-of-fit indices were obtained: Root Mean Square Error of Approximation (RMSEA) = 0.064, Tucker-Lewis Index (TLI) = 0.922, and Comparative Fit Index (CFI) = 0.931 for the classroom and RMSEA = 0.076, TLI = 0.912, and CFI = 0.923 for clinical setting. The Cronbach's alpha of the scale was 0.936 for the classroom and 0.949 for the clinical setting. Conclusions: The Persian version of H-PEPSS includes six factors with 23 items. This scale is a valid and reliable instrument for assessing patient safety education in the classroom and clinical setting.